Albright’s hereditary osteodystrophy (pseudohypoparathyroidism type Ia): clinical case with a novel mutation of GNAS1 - Garavelli, L.; Pedori, S.; Zanacca, et al., C. (Acta Biomedica Atenei Parmensis, 2005)
Albright’s hereditary osteodystrophy is characterized by ectopic calcification and ossification, round face, short hands and feet with short terminal phalanges, short metacarpals (especially 4th and 5th) and absence of the 4th knuckle (brachydactyly type E) [1] . Here we describe a case that recently came to our attention of a girl suffering from seizures caused by hypocalcaemia, in which the clinical diagnosis of Albright’s hereditary osteodystrophy and Pseudohypoparathyroidism (PHP) (Pseudohypoparathyroidism Ia) was confirmed by DNA molecular analysis. This analysis revealed a novel mutation of GNAS1, resulting in the nonsense mutation of exon 13 (CAG→TAG, codon 384). This result expands the spectrum of GNAS1 mutations associated with this disorder.